IMPACT OF CHRONIC VIRAL HEPATITIS ON COVID-19: CLINICAL COURSE AND RISK FACTORS FOR POOR OUTCOME - Mitrović, Nikola; Nikolić, Nataša; Filipović, Ana; Vujović, Ankica; Karić, Uroš; Šabanović, Miloš; Milošević, Ivana (Medical Research, 2024)
Introduction/Aim: The impact of chronic viral hepatitis on COVID-19 has not been fully clarified so far. The aim of the work was to analyze the clinical features, course and outcome of COVID-19 in patients with chronic viral hepatitis and to determine the risk factors for an unfavorable outcome. Methods: A case-control study was conducted in which case group included patients with chronic viral hepatitis suffering from COVID-19, and control group included patients with chronic liver diseases of other etiology, matched in relation to the stage of the liver disease. All subjects were treated in the Infectious Disease Clinic in Belgrade from March 1, 2020 to March 1, 2022. Results: 75 patients with chronic liver diseases suffering from COVID-19 were analyzed, 25 with chronic viral hepatitis (13 HBV, 12 HCV) - case group, and 50 subjects in the control group. In case group, there were more males (76% vs. 72%) and younger age (53.5±15.1 vs. 57.9±13.4 years), in control group more overweight patients (36% vs. 20%). In relation to comorbidities, there were more subjects with endocrinological diseases in control group. The groups didn’t differ in terms of the severity of clinical features and outcome of COVID-19. Risk factors for severe form of COVID-19 and lethal outcome were: cirrhosis, active liver disease, high fever, dyspnea, and protective was vaccination against COVID-19. Conclusion: The course and outcome of COVID-19 is similar in people with chronic liver diseases. Risk factors for a poor outcome are advanced liver disease and dyspnea, while vaccination is protective.